Transmission of risk preferences from mothers to daughters - Alan, S; Baydar, N; Boneva, T; Crossley, T; Ertac, S (Elsevier, 2016)
We study the transmission of risk attitudes in a unique survey of mothers and children in which both participated in an incentivized risk preference elicitation task. We document that risk preferences are correlated between mothers and children when the children are just 7–8 years old. This correlation is only present for daughters. We further show that a measure of maternal involvement is a strong moderator of the association between mothers’ and daughters’ risk tolerance. This is consistent with a role for socialization and parental investment in the intergenerational transmission of risk preferences.